In-situ preparation of poly(2-ethyl-2-oxazoline)/clay nanocomposites via living cationic ring-opening polymerization. (March 2017) - Ozkose, Umut Ugur; Altinkok, Cagatay; Yilmaz, Ozgur; Alpturk, Onur; Tasdelen, Mehmet Atilla
Graphical abstract: Highlights: In situ preparation of a series of poly(2-ethyl-2-oxazoline)/clay nanocomposites are achieved by living cationic ring-opening polymerization. The living nature of the process produces well-defined polymers between silicate interlayers and leading to nanocomposite formation. Based on XRD and TEM results, all nanocomposites have mixed morphologies containing non-uniform intercalated layers and exfoliated single layers isolated from any stacks in the polymer matrix and improved thermal properties compared to the pure poly(2-ethyl-2-oxazoline). Abstract: The present study reports for the first time the preparation of poly(2-ethyl-2-oxazoline)/clay nanocomposites. The tosyl-functionalized montmorillonite clay is utilized as initiator for the living cationic ring-opening polymerization of 2-ethyl-2-oxazoline, which triggers the delamination of silicate layers in the polymer matrix and leading to nanocomposite formation. The living nature of the polymerization has been confirmed by kinetic studies. The morphology and thermal properties of nanocomposite have been evaluated using X-ray diffraction, transmission electron microscopy, differential scanning calorimeter and thermogravimetric analysis. All nanocomposite samples have a mixed exfoliated/intercalated silicate layers and an improved thermal stability compared to pure poly(2-ethyl-2-oxazoline).